Avalanche Carrier Multiplication in Multilayer Black Phosphorus and Avalanche Photodetector. Issue 38 (7th August 2019) - Jia, Jingyuan; Jeon, Jaeho; Park, Jin‐Hong; Lee, Byoung Hun; Hwang, Euyheon; Lee, Sungjoo
Abstract: A highly sensitive avalanche photodetector (APD) is fabricated by utilizing the avalanche multiplication mechanism in black phosphorus (BP), where a strong avalanche multiplication of electron–hole pairs is observed. Owing to the small bandgap (0.33 eV) of the multilayer BP, the carrier multiplication occurs at a significantly lower electric field than those of other 2D semiconductor materials. In order to further enhance the quantum efficiency and increase the signal‐to‐noise (S/N) ratio, Au nanoparticles (NPs) are integrated on the BP surface, which improves the light absorption by plasmonic effects. The BP–Au‐NPs structure effectively reduces both dark current (≈10 times lower) and onset of avalanche electric field, leading to higher carrier multiplication, photogain, quantum efficiency, and S/N ratio. For the BP–Au‐NPs APD, it is obtained that the external quantum efficiency (EQE) is 382 and the responsivity is 160 A W ‐1 at an electric field of 5 kV cm ‐1 (Vd ≈ 3.5 V, note that for the BP APD, EQE = 4.77 and responsivity = 2 A W ‐1 obtained at the same electric field). The significantly increased performance of the BP APD is promising for low‐power‐consumption, high‐sensitivity, and low‐noise photodevice applications, which can enable high‐performance optical communication and imaging systems. Abstract : A highly sensitive/efficient black phosphorus‐based avalanche photodetector fully utilizes the avalanche carrier multiplication mechanism. In black phosphorus, a strong avalanche multiplication of electron–hole pairs is observed and the multiplication occurs at a much lower electric field than other 2D semiconductor materials. The significantly increased device performance is promising for low‐power‐consumption, high‐sensitivity, and low‐noise photodevice applications.